Penggunaan Metode Inverse Regression dalam Memprediksi Jumlah Ternak Puyuh Berdasarkan Keuntungan Hasil Produksi Peternakan Laura - Miftahul Hayati; Suherman Suherman; Helma Helma (UNIVERSITAS NEGERI PADANG, 2018)
Abstract - Puyuh is a kind of livestock which is popularly known as one of some animal protein source. The farmer should be able to formulate a right way to gain profit from the production which is proper with the need. Thus, it is important to make a calculation to predict the number of the livestock which have to be farmed according to profit of the production by using Inverse Regression classical prediction method that it can be predicted the value of gained from response variable at the prediction model. This research is aimed to determine the model and interval of prediction to predict the number of puyuh which have to be farmed according to profit of the production. From the result of the Inverse Regression classical prediction method and interval of the prediction which is got can be interpreted that the quantity of production number which is needed depends on profit of the production and average of number of puyuh farming production.